STANDARD CLAUSES IN EMPLOYMENT AGREEMENT BASED ON THE FREEDOM OF CONTRACT PRINCIPLE - Lidia Febrianti; Thamrin S; Puti Mayang Seruni (Jurnal Cendekia Hukum, 2022)
An employment agreement that doesn’t contain balanced rights and obligations between the parties will bring losses to one of the parties. The imbalance in the rights and obligations in the employment agreement is because the employer usually uses standard clauses. Thus eliminating the opportunity for workers to participate freely in determining the contents of the agreement. The freedom left for the workers is in the form of a choice between accepting or rejecting. This study aims to identify how the position of standard clauses in employment agreements based on the principle of freedom of contract. This research is a normative research conducted by examining library materials or secondary data. The research show that the existence of standard clauses in the agreement does limit the essence of the principle of freedom of contract. Standard clauses in employment agreements are made because of business efficiency which is also possible to arise due to an unequal position between the  parties. The principle of freedom of contract in an employment agreement isn’t included in the four legal conditions that must be met in an agreement. So that the validity of employment agreements that made without the principle of freedom of contract will remain valid.